Networks and firm location - Pontes, José Pedro (2022)
This paper models the decision of vertically linked firms to build either partitioned or connected networks of supply of an intermediate good. In each case, there is a correlation between the locations of upstream and downstream firms. Input specificity is related to both variable costs (transport costs of the input) and fixed costs (learning costs of the use of the input). When both are low, a connected network emerges, whereas, in the opposite case, we find a partitioned pattern. In the boundary region, there are multiple equilibria, either asymmetric (mixed network) or symmetric